Samarium cobalt magnet and preparation method thereof

By adjusting the sintering, solid solution and tempering processes, the cracking problem caused by the high brittleness of samarium-cobalt magnets is solved, which significantly improves its mechanical properties, reduces production costs, and is suitable for large-scale production.

CN119541981APending Publication Date: 2025-02-28HANGZHOU PERMANENT MAGNET GRP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411593213.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Due to its high brittleness, samarium-cobalt magnets are prone to cracking during manufacturing and processing, which increases production costs and limits their application range.

Method used

By adjusting the sintering temperature, solid solution temperature and tempering conditions, the specific steps include smelting of ingredients, crushing and powder making, forming and isostatic pressure, sintering, solid solution and tempering, and the sintering temperature is 1230-2 (WFe×100)±2℃, the solid solution temperature is 1230-4 (WFe×100)±2℃, the first stage of tempering temperature is 830℃-850℃, and the second stage of tempering temperature is 380℃-420℃, to improve the mechanical properties of samarium-cobalt magnets.

Benefits of technology

It significantly improves the mechanical properties of samarium-cobalt magnets, reduces operating costs and energy consumption, is suitable for large-scale production without the need for additional elements or additional processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119541981A_ABST
    Figure CN119541981A_ABST
Patent Text Reader

Abstract

The invention relates to a samarium-cobalt magnet and a preparation method thereof. The preparation method of the samarium-cobalt magnet comprises the steps of burdening and smelting, crushing and pulverizing, forming and isostatic pressing, sintering, solid solution and tempering, in the steps of sintering, solid solution and tempering, the sintering temperature T sintering is 1230-2 (WFe * 100) + / -2 DEG C, the solid solution temperature T solid is 1230-4 (WFe * 100) + / -2 DEG C, WFe is the mass fraction of Fe in the samarium-cobalt magnet, WFe is smaller than or equal to 20%, and the balance is Fe. The tempering comprises first-stage tempering and second-stage tempering, the temperature of the first-stage tempering is 830-850 DEG C, the time of the first-stage tempering is 4-8 hours, the temperature of the second-stage tempering is 380-420 DEG C, and the time of the second-stage tempering is 2-4 hours. According to the preparation method of the samarium-cobalt magnet, the mechanical property of the samarium-cobalt magnet can be remarkably improved, and meanwhile operation is easy, energy consumption is low, and cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permanent magnetic materials, in particular to a samarium cobalt magnet and a preparation method thereof. Background Art

[0002] Due to its high brittleness, samarium cobalt magnets are prone to cracking during the manufacturing and processing process, which increases the production cost of samarium cobalt magnets and also limits their service environment to a certain extent, which is not conducive to the widespread application of samarium cobalt magnets.

[0003] At present, in view of the problem that samarium cobalt magnets are brittle and easy to crack, technicians in this field have made many explorations and improvements. For example, after the aging period, patent CN118507238A performs multiple heat treatments on the samarium cobalt blank, and applies magnetic fields and stresses to achieve a synergistic improvement in magnetic properties and mechanical properties, but multiple heat treatments increase process time and power consumption, and the method of applying magnetic fields and stresses is also difficult to use in large-scale production; patent CN117912831A improves the mechanical properties of samarium cobalt magnets by mixing samarium cobalt magnetic powders of different compositions and different particle sizes, but this method is relatively complicated and has high operating costs; and patent CN117711793A promotes the diffusion of copper elements by slowing down the rate of the aging cooling stage, so that the copper elements in the cell wall phase are fully segregated, thereby improving its mechanical properties, but the slow cooling rate will increase power consumption and increase production costs. Summary of the invention

[0004] Based on this, it is necessary to provide a samarium cobalt magnet and a preparation method thereof to address the above problems. The preparation method of the samarium cobalt magnet can significantly improve the mechanical properties of the samarium cobalt magnet, and at the same time, the operation is simple, the energy consumption is low, and the cost is low.

[0005] A method for preparing a samarium-cobalt magnet comprises a batching and smelting step, a crushing and powdering step, a molding and isostatic pressing step, a sintering, a solid solution and a tempering step. In the sintering, the solid solution and the tempering step, the sintering temperature T 烧 1230-2(W Fe ×100)±2℃, solution temperature T 固 1230-4(W Fe ×100)±2℃, where W Fe is the mass fraction of Fe element in the composition of SmCo magnet, W Fe ≤20%, and the tempering includes the first tempering and the second tempering, the first tempering temperature is 830℃-850℃, the first tempering time is 4h-8h, the second tempering temperature is 380℃-420℃, and the second tempering time is 2h-4h.

[0006] In one embodiment, the sintering temperature T 烧The temperature is 1190℃-1210℃, and the sintering time is 2h-4h.

[0007] In one embodiment, the solution temperature T 固 The temperature is 1150℃-1190℃, and the solution time is 2h-8h.

[0008] In one embodiment, after the first stage of tempering is completed, the temperature is lowered to 380°C-420°C at a rate of 0.3°C / min-0.8°C / min for the second stage of tempering.

[0009] In one of the embodiments, in the batching and smelting step, the ingredients are prepared according to the formula of samarium cobalt magnets, wherein, based on 100% by weight, the formula of the samarium cobalt magnets includes: 24%-28% Sm, 10%-20% Fe, 3%-6% Cu, 2%-4% Zr, and the rest is Co.

[0010] In one embodiment, in the crushing and powder making step, a powder is obtained after crushing, and the average particle size of the powder is 4 μm-5 μm.

[0011] In one embodiment, the crushing includes mechanical crushing and air flow grinding performed in sequence, wherein the average particle size of the powder after mechanical crushing is 20 μm-300 μm, and the rotation speed of the air flow grinding is 3000 r / min-4000 r / min.

[0012] In one embodiment, in the molding and isostatic pressing steps, the magnetic field of the molding press is 1T-3T, the isostatic pressing pressure is 100MPa-300MPa, and the holding time is 5min-20min.

[0013] In one embodiment, during the molding and isostatic pressing steps, the green density after molding is 3.8 g / cm 3 -4.2g / cm 3 The green density after isostatic pressing is 5.0g / cm 3 -5.4g / cm 3 .

[0014] A samarium cobalt magnet prepared by the samarium cobalt magnet preparation method as described above.

[0015] The method for preparing a samarium cobalt magnet of the present invention is aimed at the production of a samarium cobalt magnet with an iron mass fraction of less than 20%. By means of a relationship between sintering temperature, solid solution temperature and the iron content in the samarium cobalt magnet, the sintering temperature and the solid solution temperature can be adjusted to an optimal temperature according to the iron content in the samarium cobalt magnet. By adjusting the sintering temperature, a samarium cobalt magnet with a higher density can be obtained without reducing the residual magnetism. The adjustment of the solid solution temperature can control the coercive force of the samarium cobalt magnet and avoid the rapid growth of grains due to excessively high solid solution temperature, thereby effectively improving the mechanical properties of the samarium cobalt magnet. Furthermore, by controlling the tempering conditions, high-temperature short-time tempering is performed, that is, the first-stage tempering temperature is appropriately increased to shorten the holding time, which can not only ensure that the samarium cobalt magnet has a higher coercive force, but also the shortening of the holding time is conducive to preventing the grains from continuing to grow, thereby improving the mechanical properties of the samarium cobalt magnet. Therefore, under the synergistic effect of sintering temperature, solution temperature and high temperature short-time tempering, the grain size of the samarium cobalt magnet can be refined and the mechanical properties of the samarium cobalt magnet can be significantly improved.

[0016] In addition, in the preparation method of the samarium cobalt magnet of the present invention, only the sintering, solid solution and tempering processes are adjusted, and no other elements need to be added, and no additional steps need to be added. The tempering time is also shortened, and the sintering and solid solution temperatures are regulated to be optimal temperatures, which is beneficial to avoid using higher sintering temperatures and solid solution temperatures. Therefore, compared with traditional technologies, the preparation method of the samarium cobalt magnet of the present invention is simple to operate, has low energy consumption and low cost, and is suitable for application in enterprise production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 is a metallographic image of the samarium cobalt magnet prepared in Example 1 of the present invention;

[0019] Figure 2 is a metallographic image of the samarium cobalt magnet prepared in Example 4 of the present invention;

[0020] Figure 3 is a metallographic image of the samarium cobalt magnet prepared in Comparative Example 2 of the present invention;

[0021] Figure 4 is a metallographic image of the samarium cobalt magnet prepared in Comparative Example 3 of the present invention;

[0022] Figure 5 This is a metallographic image of the samarium cobalt magnet prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0023] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0025] After long-term and in-depth research, the applicant found that in the production of samarium cobalt magnets with an iron mass fraction of less than 20%, there is a specific relationship between the sintering temperature and the solid solution temperature and the iron content in the samarium cobalt magnets. For example, the sintering temperature T 烧 1230-2(W Fe ×100)±2℃, solution temperature T 固 1230-4(W Fe ×100)±2℃, where W Fe is the mass fraction of Fe element in the composition of SmCo magnet. According to the corresponding relationship, the sintering temperature and the solid solution temperature can be adjusted to the optimal temperature according to the iron content in the SmCo magnet, so as to improve the mechanical properties of the SmCo magnet without damaging the magnetic properties of the SmCo magnet.

[0026] To this end, the preparation method of the samarium cobalt magnet provided by the present invention comprises a batching and smelting step, a crushing and powdering step, a molding and isostatic pressing step, a sintering, a solid solution and a tempering step. In the sintering, solid solution and tempering steps, the sintering temperature T 烧 1230-2(W Fe ×100)±2℃, solution temperature T 固 1230-4(W Fe ×100)±2℃, where W Fe is the mass fraction of Fe element in the composition of SmCo magnet, W Fe ≤20%, preferably 10%≤W Fe≤20%. It can be understood that in the present invention, the sintering temperature and the solid solution temperature can be adjusted to the optimal temperature according to the relationship between the sintering temperature, the solid solution temperature and the iron content in the samarium cobalt magnet, and according to the iron content in the samarium cobalt magnet, wherein by adjusting the sintering temperature, a samarium cobalt magnet with higher density can be obtained without reducing the remanence; and the adjustment of the solid solution temperature can control the coercive force of the samarium cobalt magnet, while avoiding the rapid growth of grains due to excessively high solid solution temperature, and can effectively improve the mechanical properties of the samarium cobalt magnet.

[0027] Furthermore, the tempering includes a first stage of tempering and a second stage of tempering, the first stage of tempering temperature is 830°C-850°C, the first stage of tempering time is 4h-8h, the second stage of tempering temperature is 380°C-420°C, and the second stage of tempering time is 2h-4h; by controlling the tempering conditions, high-temperature short-time tempering is performed, that is, the first stage of tempering temperature is appropriately increased to shorten its holding time, which can effectively avoid the influence on the diffusion of Cu element, optimize the squareness of the samarium cobalt magnet, ensure that the samarium cobalt magnet has a higher coercive force, and the shortening of the holding time is conducive to preventing the grains from continuing to grow, thereby improving the mechanical properties of the samarium cobalt magnet.

[0028] Therefore, under the synergistic effect of sintering temperature, solution temperature and high temperature short-time tempering, the present invention can refine the grain size of the samarium cobalt magnet with an iron content below 20%, and significantly improve the mechanical properties of the samarium cobalt magnet.

[0029] In addition, in the preparation method of the samarium cobalt magnet of the present invention, only the sintering, solid solution and tempering processes are adjusted, and no other elements need to be added, and no additional steps need to be added. The tempering time is also shortened, and the sintering and solid solution temperatures are regulated to be optimal temperatures, which is beneficial to avoid using higher sintering temperatures and solid solution temperatures. Therefore, compared with traditional technologies, the preparation method of the samarium cobalt magnet of the present invention is simple to operate, has low energy consumption and low cost, and is suitable for application in enterprise production.

[0030] Therefore, the preparation method of the samarium cobalt magnet of the present invention can significantly improve the mechanical properties of the samarium cobalt magnet.

[0031] At the same time, it is simple to operate, has low energy consumption and low cost.

[0032] Moreover, in the present invention, the coercive force of the samarium cobalt magnet can be controlled by adjusting the solid solution temperature, so it is conducive to preparing samarium cobalt magnets of various brands to meet the requirements of different customers for different magnet properties.

[0033] Optionally, the sintering temperature T 烧 The temperature is 1190℃-1210℃, and the sintering time is 2h-4h. Such a setting is conducive to further improving the density of the samarium cobalt magnet, while better avoiding the excessive grain size of the samarium cobalt magnet and reducing the volatilization of the samarium element, so that the samarium cobalt magnet has both good magnetic properties and mechanical properties.

[0034] Optionally, the solution temperature T 固 The temperature is 1150℃-1190℃, and the solution time is 2h-8h. Such a setting can effectively inhibit the precipitation of other phases in the solid solution state of the samarium cobalt magnet, which is conducive to obtaining a complete 1:7 phase, and can further optimize the coercive force and squareness of the samarium cobalt magnet. At the same time, it can better avoid the rapid growth of grains due to high solution temperature, and better improve the mechanical properties of the samarium cobalt magnet.

[0035] Optionally, after the first stage of tempering is completed, the temperature is lowered to 380°C-420°C at a rate of 0.3°C / min-0.8°C / min for the second stage of tempering. This setting can effectively control the cooling time, avoid the influence on the diffusion of copper elements in the samarium cobalt magnet, and is conducive to ensuring that the samarium cobalt magnet has a good coercive force.

[0036] In the present invention, the sintering, solid solution and tempering steps are as follows: the green body obtained in the forming and isostatic pressing steps is placed in a sintering furnace for sintering and solid solution in sequence, cooled to room temperature after solid solution and taken out of the furnace, and then tempered, and after tempering, cooled to room temperature with the furnace and taken out of the furnace to obtain a samarium cobalt magnet.

[0037] Specifically, the green body obtained in the forming and isostatic pressing steps is placed in a sintering furnace, and after being vacuumed for 2h-4h, it is heated and set into four insulation sections to discharge the adsorbed gas in the blank, wherein the temperature of the first insulation section is 80℃-100℃, the temperature of the second insulation section is 250℃-300℃, the temperature of the third insulation section is 500℃-600℃, and the temperature of the fourth insulation section is 900℃-1000℃, and the heating rate of adjacent insulation sections is 2℃ / min-4℃ / min, and the insulation time of each section is 1h. After the insulation is completed, the temperature is then increased to 1130℃-1170℃ at a heating rate of 2℃ / min-4℃ / min, and the insulation time is 1h as pre-sintering, and then the temperature is continued to be increased to the sintering temperature, argon is filled and the pressure in the sintering furnace is controlled to reach 2.0×10 4 Pa-4.0×10 4 After Pa, sintering is carried out, and then solid solution is carried out. After solid solution, the temperature is quickly cooled to room temperature by air cooling and then taken out of the furnace. After taking out of the furnace, it is sent to a tempering furnace for tempering. After tempering, it is cooled with the furnace to room temperature and then taken out of the furnace to obtain a samarium cobalt magnet.

[0038] In the present invention, the process of the ingredients smelting step, the crushing and powdering step, the molding and isostatic pressing step is not specifically limited. The above steps can adopt any process method in the prior art. For example, each step can be as follows:

[0039] In the batching and smelting step, the ingredients are batched according to the formula of the samarium cobalt magnet, and then smelted and cast into samarium cobalt ingots or sheets.

[0040] Optionally, based on 100% by weight, the formula of the samarium cobalt magnet includes: 24%-28% Sm, 10%-20% Fe, 3%-6% Cu, 2%-4% Zr, and the rest is Co.

[0041] In one embodiment, the smelting steps are as follows: placing the ingredients of the samarium cobalt magnet in a smelting furnace, evacuating, preheating, filling with inert gas, and smelting to obtain an alloy solution, then casting the alloy solution into samarium cobalt ingots or sheets, cooling to room temperature and taking out of the furnace.

[0042] Optionally, the inert gas is selected from at least one of argon, helium, neon or krypton.

[0043] In one embodiment, the specific steps of vacuuming, preheating, filling with inert gas, and smelting to obtain the alloy solution are as follows: when vacuuming to 8Pa-12Pa, turn on the medium frequency, adjust the power to about half the weight of the raw materials in the furnace, preheat for 20min-30min, turn off the medium frequency when the vacuum in the furnace no longer increases, continue to vacuum to 4Pa-8Pa, fill with argon to 2.0×10 4 Pa-4.0×10 4 Pa, turn on the medium frequency again, adjust the power to about the weight value in the furnace, and smelt for 25min-30min to obtain a uniform and clear alloy liquid.

[0044] In the present invention, the crushing and powdering step is specifically as follows: the samarium-cobalt ingot or flake obtained in the batch smelting step is mechanically crushed, and then subjected to air flow grinding to obtain a powder, wherein the average particle size of the powder is 4 μm-5 μm. It can be understood that the average particle size of the powder can be selected from any value between 4 μm and 5 μm, and specifically, the average particle size of the powder includes but is not limited to: 4 μm, 4.5 μm, 5 μm. Such a setting is conducive to improving the mechanical properties of the magnet.

[0045] Optionally, the average particle size of the powder after mechanical crushing is 20 μm-300 μm, and the rotation speed of the airflow milling is 3000 r / min-4000 r / min. With such an arrangement, the average particle size of the powder can be effectively controlled to be 4 μm-5 μm.

[0046] In the present invention, the molding and isostatic pressing steps are specifically as follows: the powder obtained in the crushing and powder making step is fed into a molding press to form blocks, and then isostatically pressed to further increase the green body density.

[0047] The magnetic field of the molding press is 1T-3T, the isostatic pressure is 100MPa-300MPa, and the holding time is 5min-20min. Such a setting is conducive to improving the mechanical properties and magnetic properties of the magnet.

[0048] Optionally, the green density after molding is 3.8 g / cm 3 -4.2g / cm 3 The green density after isostatic pressing is 5.0g / cm 3 -5.4g / cm 3 Such an arrangement is conducive to obtaining a magnet with high density and better improving the mechanical and magnetic properties of the magnet.

[0049] At the same time, the present invention also provides a samarium cobalt magnet prepared by the above-mentioned samarium cobalt magnet preparation method. The samarium cobalt magnet has good magnetic properties and good mechanical properties.

[0050] The samarium cobalt magnet and its preparation method will be further described below by the following specific examples. However, those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0051] Example 1

[0052] The ingredients were prepared according to the following formula of samarium cobalt magnets, where, by mass percentage, the mass fraction of Sm was 26%, the mass fraction of Co was 49%, the mass fraction of Fe was 16%, the mass fraction of Cu was 6%, and the mass fraction of Zr was 3%. Then, the mixture was placed in a melting furnace, vacuumed to 10.0 Pa, the intermediate frequency preheating exhaust was turned on, the power was adjusted to half the weight of the raw materials, the intermediate frequency was turned off after 24 minutes, the vacuum was continued to be pumped to 6.0 Pa, and argon was filled to make the pressure in the furnace 3.0×10 4 MPa, turn on the medium frequency again and adjust the smelting power to the weight value of the raw materials. After smelting for 27 minutes, a uniform and clear alloy melt is obtained. The alloy solution is then poured into a condensing mold to cool, and then cooled to room temperature and taken out of the furnace to obtain a samarium-cobalt alloy ingot.

[0053] The samarium-cobalt alloy ingot obtained above was mechanically crushed to obtain a coarse powder, wherein the average particle size was about 150 μm, and then subjected to air flow grinding to obtain a fine powder, wherein the air flow grinding speed was 3500 r / min, and the average particle size of the fine powder was about 4.5 μm.

[0054] The fine powder obtained above was sent to a press for orientation molding, wherein the orientation magnetic field was 2T, and then isostatic pressing was performed to obtain a green body, wherein the isostatic pressing pressure was 250 MPa, the holding time was 10 min, and the green body density was 5.0 g / cm 3 .

[0055] The green body obtained above was placed in a sintering furnace, and after being vacuumed for 3 hours, it was heated. At 100°C, 300°C, 550°C, and 950°C, insulation sections were set to discharge the adsorbed gas in the green body. The heating rate was 3°C / min, and the temperature was kept for 1 hour. Then, the temperature was raised to 1150°C at a heating rate of 3°C / min, and the temperature was kept for 1 hour as pre-sintering. Then, the temperature was continued to rise to the sintering temperature, and argon was filled and the pressure in the sintering furnace was controlled to reach 2.0×10 4 Pa, sintering is carried out after that, wherein the sintering temperature is 1200℃, and the sintering time is 3h. After sintering, solid solution is carried out, wherein the solid solution temperature is 1170℃, and the solid solution time is 4h. After solid solution, it is quickly cooled to room temperature by air cooling and then taken out of the furnace. After being taken out of the furnace, it is sent to the tempering furnace, wherein the first tempering temperature is 840℃, and the holding time is 6h. Then it is cooled to 400℃ at a rate of 0.7℃ / min. The second tempering is carried out and the heat preservation time is 4h. Then it is cooled to room temperature with the furnace and taken out of the furnace to obtain the samarium cobalt magnet.

[0056] Example 2

[0057] The ingredients were prepared according to the following formula of samarium cobalt magnets, where, by mass percentage, the mass fraction of Sm was 24%, the mass fraction of Co was 61%, the mass fraction of Fe was 10%, the mass fraction of Cu was 3%, and the mass fraction of Zr was 2%. Then, the magnets were placed in a melting furnace, evacuated to 10.0 Pa, the intermediate frequency preheating exhaust was turned on, the power was adjusted to half the weight of the raw materials, the intermediate frequency was turned off after 23 minutes, the vacuum was continued to be evacuated to 6.0 Pa, and argon was filled to make the pressure in the furnace 3.0×10 4 MPa, turn on the medium frequency again and adjust the smelting power to the weight value of the raw materials. After smelting for 25 minutes, a uniform and clear alloy melt is obtained. The alloy solution is then poured into a condensing mold to cool, and then cooled to room temperature and taken out of the furnace to obtain a samarium-cobalt alloy ingot.

[0058] The samarium-cobalt alloy ingot obtained above was mechanically crushed to obtain a coarse powder, wherein the average particle size was about 30 μm, and then subjected to air flow grinding to obtain a fine powder, wherein the air flow grinding speed was 4000 r / min, and the average particle size of the fine powder was about 4 μm.

[0059] The fine powder obtained above was sent to a press for orientation molding, wherein the orientation magnetic field was 1T, and then isostatic pressing was performed to obtain a green body, wherein the isostatic pressing pressure was 100 MPa, the holding time was 20 min, and the green body density was 5.1 g / cm 3 .

[0060] The green body obtained above was placed in a sintering furnace, and after being vacuumed for 3 hours, it was heated. At 100°C, 300°C, 550°C, and 950°C, insulation sections were set to discharge the adsorbed gas in the green body. The heating rate was 3°C / min, and the temperature was kept for 1 hour. Then, the temperature was raised to 1150°C at a heating rate of 3°C / min, and the temperature was kept for 1 hour as pre-sintering. Then, the temperature was continued to rise to the sintering temperature, and argon was filled and the pressure in the sintering furnace was controlled to reach 2.0×10 4 Pa, sintering is carried out after that, wherein the sintering temperature is 1210℃, and the sintering time is 2h. After sintering, solid solution is carried out, wherein the solid solution temperature is 1190℃, and the solid solution time is 2h. After solid solution, it is quickly cooled to room temperature by air cooling and then taken out of the furnace. After being taken out of the furnace, it is sent to the tempering furnace, wherein the first tempering temperature is 830℃, and the holding time is 8h. Then it is cooled to 390℃ at a rate of 0.6℃ / min. The second tempering is carried out and the heat preservation time is 4h. Then it is cooled to room temperature with the furnace and taken out of the furnace to obtain the samarium cobalt magnet.

[0061] Example 3

[0062] The ingredients are prepared according to the following formula of samarium cobalt magnets, wherein, by mass percentage, the mass fraction of Sm is 28%, the mass fraction of Co is 42%, the mass fraction of Fe is 20%, the mass fraction of Cu is 6%, and the mass fraction of Zr is 4%. Then, the magnets are placed in a melting furnace, evacuated to 10.0 Pa, the intermediate frequency preheating exhaust is turned on, the power is adjusted to half the weight of the raw materials, the intermediate frequency is turned off after 25 minutes, the vacuum is continued to be evacuated to 6.0 Pa, and argon is filled to make the pressure in the furnace 3.0×10 4 MPa, turn on the medium frequency again and adjust the smelting power to the weight value of the raw materials. After smelting for 29 minutes, a uniform and clarified alloy melt is obtained. The alloy solution is then poured into a condensing mold for cooling, and cooled to room temperature before being taken out of the furnace to obtain a samarium-cobalt alloy ingot.

[0063] The samarium-cobalt alloy ingot obtained above was mechanically crushed to obtain a coarse powder, wherein the average particle size was about 300 μm, and then subjected to air flow grinding to obtain a fine powder, wherein the air flow grinding speed was 3000 r / min, and the average particle size of the fine powder was about 5 μm.

[0064] The fine powder obtained above was sent to a press for orientation molding, wherein the orientation magnetic field was 3T, and then isostatic pressing was performed to obtain a green body, wherein the isostatic pressing pressure was 300MPa, the holding time was 6min, and the green body density was 5.3g / cm 3 .

[0065] The green body obtained above was placed in a sintering furnace, and after being vacuumed for 3 hours, it was heated. At 100°C, 300°C, 550°C, and 950°C, insulation sections were set to discharge the adsorbed gas in the green body. The heating rate was 3°C / min, and the temperature was kept for 1 hour. Then, the temperature was raised to 1150°C at a heating rate of 3°C / min, and the temperature was kept for 1 hour as pre-sintering. Then, the temperature was continued to rise to the sintering temperature, and argon was filled and the pressure in the sintering furnace was controlled to reach 2.0×10 4 Pa, sintering is carried out after that, wherein the sintering temperature is 1190℃, and the sintering time is 4h. After sintering, solid solution is carried out, wherein the solid solution temperature is 1150℃, and the solid solution time is 8h. After solid solution, it is quickly cooled to room temperature by air cooling and then taken out of the furnace. After being taken out of the furnace, it is sent to the tempering furnace, wherein the first tempering temperature is 850℃, and the holding time is 4h. Then it is cooled to 420℃ at a rate of 0.4℃ / min. The second tempering is carried out and the heat preservation time is 2h. Then it is cooled to room temperature with the furnace and taken out of the furnace to obtain the samarium cobalt magnet.

[0066] Example 4

[0067] The only difference between Example 4 and Example 1 is that the sintering temperature is 1198° C. and the sintering time is 2 h; the solid solution temperature is 1168° C. and the solid solution time is 2 h. The other conditions are the same, and a samarium cobalt magnet is obtained.

[0068] Example 5

[0069] The only difference between Example 5 and Example 1 is that the temperature is lowered to 400° C. at a rate of 0.2° C. / min, and the other conditions are the same to obtain a samarium cobalt magnet.

[0070] Example 6

[0071] The only difference between Example 6 and Example 1 is that the temperature is lowered to 400° C. at a rate of 1° C. / min, and the other conditions are the same to obtain a samarium cobalt magnet.

[0072] Comparative Example 1

[0073] The only difference between Comparative Example 1 and Example 1 is that the ingredients are prepared according to the following formula of samarium cobalt magnet, wherein, in terms of mass percentage, the mass fraction of Sm is 26%, the mass fraction of Co is 40%, the mass fraction of Fe is 25%, the mass fraction of Cu is 6%, and the mass fraction of Zr is 3%, and the other conditions are the same, thereby obtaining a samarium cobalt magnet.

[0074] Comparative Example 2

[0075] The only difference between Comparative Example 2 and Example 1 is that the sintering temperature is 1210° C. and the sintering time is 3 h. The other conditions are the same, and a samarium cobalt magnet is obtained.

[0076] Comparative Example 3

[0077] The only difference between Comparative Example 3 and Example 1 is that the solution temperature is 1180° C. and the solution time is 3 h. The other conditions are the same, and a samarium cobalt magnet is obtained.

[0078] Comparative Example 4

[0079] The only difference between Comparative Example 4 and Example 1 is that the first stage tempering temperature is 820° C. and the holding time is 3 h. The other conditions are the same, and a samarium cobalt magnet is obtained.

[0080] Comparative Example 5

[0081] The only difference between Comparative Example 5 and Example 1 is that the first stage tempering temperature is 880° C. and the holding time is 3 h. The other conditions are the same, and a samarium cobalt magnet is obtained.

[0082] The blank density, magnetic properties and bending strength of the samarium cobalt magnets prepared in Examples 1-6 and Comparative Examples 1-5 were tested respectively. The test results are shown in Table 1. The test method is as follows:

[0083] Density of samarium cobalt blank: The test is conducted by hydrostatic weighing method, as follows: Weigh the samarium cobalt blank with a balance that can be accurate to four decimal places, and use P to represent the mass of the blank. Then wrap the blank with a hanging wire and place it in distilled water, and weigh it again. Use Q to represent the weight of the blank in distilled water. The density of the blank ρ can be expressed as P / (PQ)×ρ 蒸馏水 Calculated by formula.

[0084] Magnetic properties of samarium cobalt magnets: AMT-4 permanent magnet property automatic measuring instrument is used for testing, as follows: First, a small cylinder is hollowed out from the burned samarium cobalt blank using a hole-punching machine, and then the end face is processed and the surface is ground to a size of (D6×10) mm as a test sample. This test sample is placed in the test coil of AMT-4, and the size parameters are set. The magnetic properties test can be carried out to obtain the demagnetization curve and the values ​​of various magnetic parameters.

[0085] Bending strength of samarium cobalt magnet: the three-point bending method is adopted for testing, and the equipment used is WDW-100 electronic universal testing machine, which is as follows: the samarium cobalt blank is processed into a test block with a size of (20×6×5) mm, and the direction of the size of 5 mm is the magnetization direction, which is also the force direction when testing the bending strength. The test block is placed in a specified position, and the displacement rate of the indenter is 0.2 mm / min. Then the indenter is moved down until the test block is broken, and the value of the bending strength can be obtained. 20 pieces of each blank are tested, and the bending strength value given in the present invention is the average value of the bending strength of the 20 test samples.

[0086] Table 1

[0087]

[0088] From the data in Table 1, it can be seen that the blank density of Examples 1-6 and Comparative Examples 1-5 is not much different. Except for Comparative Example 1, the difference in the remanence of the magnet is also negligible. However, the bending strength of the magnet in Examples 1-6 is improved overall compared with Comparative Examples 1-5, indicating that the preparation method of the samarium cobalt magnet provided by the present invention can improve its mechanical properties without damaging the magnetic properties of the samarium cobalt magnet. Specifically, by comparing Example 1 with Comparative Examples 2-4, it can be seen that regulating the sintering temperature, the solution temperature and the high temperature short-time tempering can improve the mechanical properties of the magnet to a certain extent; by comparing Example 1 with Comparative Example 5, it can be seen that when the temperature of the first stage tempering is too high, the coercive force and H of the magnet are affected. k It is not conducive to the improvement of; in the comparison of the various embodiments, it can be seen that the blank density of embodiments 2 and 3 is similar to that of embodiment 1, but the difference in iron content leads to obvious changes in remanence and magnetic energy product. The bending strength in embodiment 2 is low because its sintering and solid solution temperatures are high and the grain growth is more obvious, while embodiment 3 is just the opposite; the coercive force of the magnet in embodiment 4 is slightly low, because its solid solution temperature is low, the solid solution time is short, and full solid solution is not achieved; the tempering cooling rate in embodiment 5 is too slow, and the magnetic properties are not improved, but the mechanical properties have a certain improvement effect; the tempering cooling rate in embodiment 6 is too fast, and the copper element is not fully diffused into the cell wall phase, so the coercive force is low, which is not conducive to the improvement of mechanical properties.

[0089] Figure 1-Figure 5 The metallographic images of the samarium cobalt magnets of Example 1, Example 4, Comparative Example 2, Comparative Example 3, and Comparative Example 4 respectively correspond to each other. It can be seen from each figure that Figure 1 The grain size of the medium magnet is mostly within 100μm. Figure 2 The grain size of medium magnets is mostly within 50μm. Figure 3 and Figure 4 The maximum grain size of the medium magnet is about 200μm. Figure 5 The maximum grain size of the medium magnet is between 150-200 μm. Figure 1 , Figure 3 , Figure 4 , Figure 5 The grain size of the medium magnet can roughly explain the difference in the bending strength of each magnet, and it shows that the grain size of the magnet can be refined by adjusting the sintering temperature, the solid solution temperature, and the temperature and time of the first tempering in the present invention, thereby achieving the improvement of the mechanical properties of the samarium cobalt magnet. The coercive force of Example 4 is relatively low, but its overall grain size is low and the mechanical properties are high. It can be used as a brand to meet the needs of corresponding customers, and within the scope of the present invention, the coercive force can be improved by adjusting the solid solution temperature and time to meet the customer's needs for different coercive forces of samarium cobalt magnets.

[0090] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0091] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a samarium cobalt magnet, comprising a batching and smelting step, a crushing and powdering step, a molding and isostatic pressing step, a sintering, a solid solution and a tempering step, characterized in that: In the sintering, solution and tempering steps, the sintering temperature T 烧 1230-2(W Fe ×100)±2℃, solution temperature T 固 1230-4(W Fe ×100)±2℃, where W Fe is the mass fraction of Fe element in the composition of SmCo magnet, W Fe ≤20%, and the tempering includes the first tempering and the second tempering, the first tempering temperature is 830℃-850℃, the first tempering time is 4h-8h, the second tempering temperature is 380℃-420℃, and the second tempering time is 2h-4h.

2. The method for preparing a samarium cobalt magnet according to claim 1, characterized in that: The sintering temperature T 烧 The temperature is 1190℃-1210℃, and the sintering time is 2h-4h.

3. The method for preparing a samarium cobalt magnet according to claim 1, characterized in that: The solution temperature T 固 The temperature is 1150℃-1190℃, and the solution time is 2h-8h.

4. The method for preparing a samarium cobalt magnet according to claim 1, characterized in that: After the first stage of tempering, the temperature is lowered to 380℃-420℃ at a rate of 0.3℃ / min-0.8℃ / min for the second stage of tempering.

5. The method for preparing a samarium cobalt magnet according to any one of claims 1 to 4, characterized in that: In the step of batching and smelting, the ingredients are batched according to the formula of the samarium cobalt magnet, wherein, based on 100% by weight, the formula of the samarium cobalt magnet includes: 24%-28% Sm, 10%-20% Fe, 3%-6% Cu, 2%-4% Zr, and the rest is Co.

6. The method for preparing a samarium cobalt magnet according to any one of claims 1 to 4, characterized in that: In the crushing and powdering step, powder is obtained after crushing, and the average particle size of the powder is 4μm-5μm.

7. The method for preparing a samarium cobalt magnet according to claim 6, characterized in that: The crushing includes mechanical crushing and air flow grinding performed in sequence, wherein the average particle size of the powder after mechanical crushing is 20μm-300μm, and the rotation speed of the air flow grinding is 3000r / min-4000r / min.

8. The method for preparing a samarium cobalt magnet according to any one of claims 1 to 4, characterized in that: In the molding and isostatic pressing steps, the magnetic field of the molding press is 1T-3T, the isostatic pressing pressure is 100MPa-300MPa, and the holding time is 5min-20min.

9. The method for preparing a samarium cobalt magnet according to any one of claims 1 to 4, characterized in that: In the molding and isostatic pressing steps, the green density after molding is 3.8g / cm 3 -4.2g / cm 3 The green density after isostatic pressing is 5.0g / cm 3 -5.4g / cm 3 .

10. A samarium cobalt magnet prepared by the method for preparing a samarium cobalt magnet according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-bending-strength samarium-cobalt sintered magnet and preparation method thereof

    CN117912831A